Patient experience of bladder cancer: A data linkage study - Snehadhar Shah; Jonathan Ince; Roger Kockelbergh (BJUI Compass)
Abstract Introduction Bladder cancer is one of the most common cancers worldwide and can be managed with a range of approaches, including conservative, medical and surgical therapies. Treatment may be associated with considerable morbidity, but despite this, little data exist to reflect patients' subsequent experience. This study aims to evaluate patients' experiences of bladder cancer care by linking data from a national cancer experience survey with data routinely collected from National Health Service (NHS) sources. This study considers patient perspectives and makes recommendations to improve the patient experience of bladder cancer care. Methods Anonymised data from the National Cancer Patient Experience Survey (NCPES) for patients who had received care for bladder cancer were collated and linked with demographic and treatment data. Questions from the NCPES were then categorised into different themes based on their content. This study focused on themes relating to lifestyle, activities of daily living (ADL), symptoms, psychological impact and body perception. Statistical analyses were used to investigate the relationship between patient reported experience, demographics and type of care received. Results NCPES data from 673 patients (487 male, 29 undisclosed) with at least T1 bladder cancer were analysed. Statistically significant differences were identified across the five investigated patient experience themes. No significant difference was seen in patient reported experience between bladder cancer drug treatments (such as intravesical BCG vs. intravesical chemotherapy vs. systemic chemotherapy) and radiotherapy types (curative vs. palliative). Patients treated with cystectomy had significantly worse experiences relating to body image and ADL but not when compared with patients treated with radical radiotherapy. Patients with long‐term health conditions reported worse experiences for all five themes compared with those without. Conclusion The literature surrounding the experience of patients with bladder cancer is limited. This data linkage study demonstrates the impact of bladder cancer care on five patient experience themes, including the effect of different treatment types and the presence of long‐term health conditions. While limited by sample size and data comprehensiveness, this study aims to inform clinicians and service providers of factors affecting patient experience of bladder cancer care, to stimulate service review and development.